Albert Camus, Simone Weil and the Absurd - Van Nieuwenhove, Rik (Irish theological quarterly, 2005)
According to Camus it is only in the face of the absurd - and through our unremitting revolt against it - that meaning can be generated. Espousing the Christian faith abnegates the absurd, and with it the only possible source of meaning for modem man. This critique can be addressed by engaging with Simone Weil. She develops an original dialectic of divine absence (in the laws of indifferent 'necessity' and affliction) and presence, which reflects the intra-Trinitarian unity and distance of the divine Persons, and which finds ultimate expression on the Cross of Christ. For her this dialectic does not induce revolt but a sophisticated kind of reconciliation that involves a selfless openness to, and engagement with, this world.